(untitled) (Journal of Natural Language and Linguistics, 2024)
This study aims to study the gender representation in the English Textbook-1 for Intermediate classes published by Punjab Curriculum and Textbook Board (PCTB) Lahore. Based on qualitative content analysis, the description of male and female characters throughout 15 lessons is explored in terms of roles, activities, power of dynamics, and emotional displacement of the gender of characters. The results suggest the predominance of traditional gender roles in which men are typically represented as active decision-makers, leaders and rational individuals, whereas women are characterized as passive or supportive and spend most of their time in domestic environments. While there are a few lessons that buck tradition (e.g. Mrs. Jones in ‘Thank You, M’am’ who grounds herself in a way that challenges standard female stereotypes than the norm), for most the lessons reinforces patriarchal tones. Male characters are accorded greater agency, authority, emotional depth, while female characters are absent or shown in limited nurturing roles. It is an imbalance that reflects the deep embeddedness of gender roles in the cultural and social structures of Pakistan, and in the textbook’s content. Additionally, key limitations in the study are identified, including limited visual content analysis and single textbook focus. Moreover, based on the results of the study, the paper suggests that there should be gender-sensitive content integrated in the curriculum, stronger female characters represented in the curriculum, and teachers should be trained in gender sensitivity. Finally, this study finds that though the textbook is essential in teaching, it is fragile and needs to be revised to present a more balanced and reasonable depiction of gender so it empowers students to conceive of different kinds of gender roles and fight down social presumptions that suppress both men and women.